Republic of Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
The recent global financial crisis has exposed the limitations of a conventional inflation targeting framework in insulating an economy from all shocks, and demonstrated that its rigid application may aggravate the effect of shocks on output and inflation. Possible refinements to the inflation targeting framework in Korea were investigated by taking into account developments in the financial sector. The findings indicate that incorporating financial stability considerations will ease business cycle fluctuations by mitigating the buildup of factors that lead to large fluctuations in output and inflation.